USE OF SPECIAL PSYCHIATRIC AND PSYCHOLOGICAL KNOWLEDGE DURING THE INVESTIGATION OF CRIMINAL OFFENSES RELATED TO DOMESTIC VIOLENCE (Bulletin of criminological association of Ukraine, 2024)
The article substantiates that the investigation of criminal offenses, the commission of which is connected with domestic violence, involves the use of special knowledge in various forms. Their procedural forms, such as involving an expert to conduct an examination, are implemented at the stage of a pre-trial investigation to collect procedural sources of evidence in the form of an expert's opinion. The facts of the involvement of specialists in investigative (research) actions, which is also defined as a procedural form of using special knowledge, are not unique. This is caused, firstly, by the normative principles of the participation of specialists in those procedural measures, the participants of which are minors, in particular, a teacher or a psychologist, secondly, by the need to increase the effectiveness of these actions, thirdly, by the need to provide, in particular, psychological assistance to victims of domestic violence. It was established that appointing forensic psychiatric examinations and forensic psychological examinations needs improvement because currently, the pre-trial investigation bodies do not use their capabilities fully, which sometimes significantly affects the effectiveness of the pre-trial investigation. Prospects for further scientific research in the context of the investigated issues are outlined.
Keywords: criminal proceedings; pre-trial investigation; domestic violence; specialist; expert; expertise; psychologist; forensic medical expert